Intensity‐modulated radiotherapy (IMRT) in pediatric low‐grade glioma. Issue 14 (30th April 2013) - Paulino, Arnold C.; Mazloom, Ali; Terashima, Keita; Su, Jack; Adesina, Adekunle M.; Okcu, M. Faith; Teh, Bin S.; Chintagumpala, Murali
Abstract : BACKGROUND: The objective of this study was to evaluate local control and patterns of failure in pediatric patients with low‐grade glioma (LGG) who received treatment with intensity‐modulated radiation therapy (IMRT). METHODS: In total, 39 children received IMRT after incomplete resection or disease progression. Three methods of target delineation were used. The first was to delineate the gross tumor volume (GTV) and add a 1‐cm margin to create the clinical target volume (CTV) (Method 1; n = 19). The second was to add a 0.5‐cm margin around the GTV to create the CTV (Method 2; n = 6). The prescribed dose to the GTV was the same as dose to the CTV for both Methods 1 and 2 (median, 50.4 grays [Gy]). The final method was dose painting, in which a GTV was delineated with a second target volume (2TV) created by adding 1 cm to the GTV (Method 3; n = 14). Different doses were prescribed to the GTV (median, 50.4 Gy) and the 2TV (median, 41.4 Gy). RESULTS: The 8‐year progression‐free and overall survival rates were 78.2% and 93.7%, respectively. Seven failures occurred, all of which were local in the high‐dose (≥95%) region of the IMRT field. On multivariate analysis, age ≤5 years at time of IMRT had a detrimental impact on progression‐free survival. CONCLUSIONS: IMRT provided local control rates comparable to those provided by 2‐dimensional and 3‐dimensional radiotherapy. Margins ≥1 cm added to the GTV may not be necessary, because excellent local control was achieved by adding a 0.5‐cm margin (Method 2) and by dose painting (Method 3). Cancer 2013;119:2654–2659 . © 2013 American Cancer Society . Abstract : Intensity‐modulated radiation therapy provides local control rates comparable to those achieved with 2‐dimensional and 3‐dimensional radiotherapy in pediatric patients with low‐grade glioma. Margins ≥1 cm added to the gross tumor volume to create the clinical target volume may not be necessary, because excellent local control is achieved by adding a 0.5‐cm margin to the clinical target volume and by dose painting.